THERMAL RESISTIVITY DRY-OUT CURVES FOR THIRTEEN SANDY SOILS - Oh, Hyunjun (My University, 2014)
EXECUTIVE SUMMARY The objective of this study was to identify which physical properties impact the thermal resistivity dry-out curve (TRDC) of natural sandy soils. The TRDC is a relationship between soil thermal resistivity and degree of wetness (e.g., volumetric water content, gravimetric water content, or degree of saturation). TRDCs of 13 sandy soils were investigated using modified hanging column tests. The tests were also used to investigate co-effects of the soil-water characteristic curve (SWCC), which represents the hydraulic properties of unsaturated soil. The physical properties evaluated in this research included: (1) degree of saturation, (2) soil particle size (D10 and D50), (3) fines content, (4) soil type, (5) soil density (?dmax, emax, and emin) and gradation (Cu), (6) quartz content, and (7) particle shape (sphericity and roundness). In the TRDCs, three analysis points?thermal resistivity (?) at the fully dried condition, critical degree of saturation, and fully saturated condition?were selected for analysis. Correlations between the three points of interest on the TRDC and the physical properties were supported with high-resolution images obtained by synchrotron X-ray computed tomography (CT) and statistical analysis, including, ANOVA and stepwise regression. Results included the significant effects of the measured soil physical parameters on the TRDC in addition to the well-recognized parameter of degree of saturation as reported in the literature. Impacts of degree of saturation on the TRDC were related to thermal resistivity of three phases of soil systems (?solid, ?liquid, and ?air). Due to high ?air, the highest ?soil was observed at the fully dried condition. As degree of saturation increases, thin films and liquid bridges among soil particles are formed, resulting in a rapid decrease in thermal resistivity. Near the critical degree of saturation of a TRDC, which is located near the knee point of the SWCC where moisture exists as adsorbed films (McQueen and Miller, 1977), changes in ?soil are more rapid. After liquid bridges form, ?soil decreases gradually as degree of saturation increases. The lowest ?soil was measured at the saturated condition. Soil thermal resistivity also decreased with increase in particle size as evaluated by D10 and D50. This was primarily related to size and thermal resistivity of the solid phase. In high-resolution images, for example, larger solid particles provide larger heat transfer paths, while smaller solid particles (e.g., silt-sized) consist of smaller heat transfer paths with a more tortuous void structure. Consequently, ?soil was affected by particle size as related to the thermal resistivity of the solid and void phases in addition to the tortuosity of the matrix. In contrast, ?soil increased with increasing fines content. Reasons for the effect of fines were similar to those of particle size. At a constant void ratio, soil that included higher fines content, such as SM soils, had relatively small solid particles with tortuous voids compared with SP or SW soils, which do not include significant fines content. Smaller solid particles and tortuous voids led to a decrease in ?soil. In the modified hanging column test and ANOVA, thermal resistivity values of the 13 sandy soils were unaffected by the type of sandy soil regardless of the point of comparison. Parallel with laboratory tests, statistical analyses indicate that slight differences among soil types are not statistically significant regardless of the point of interest evaluated. At the dried, critical, and saturated condition, statistical significance by soil types per ANOVA were 0.061, 0.174, and 0.268. Therefore, a larger database of soil that represents the full spectrum of gravel, silt, and clay is required to fully investigate the effect of soil type on the TRDC. The effect of soil density on TRDC was analyzed using four density parameters: (a) maximum dry unit weight (?dmax), (b) minimum void ratio (emin), (c) maximum void ratio (emax), and (d) coefficient of uniformity (Cu). Soil thermal resistivity decreased as ?dmax and Cu increased, while soil thermal resistivity increased with increasing emin and emax. In other words, ?soil decreased as soil density increased because of closer particle contacts and a reduction of the volume of air. On the other hand, ?soil increased with increase in emin and emax, which represent a decrease in soil density, due to less particle contacts and greater air volume. Because quartz is amongst the best heat conducting minerals that is common in natural soils (Winterkorn, 1962), influence of quartz content on the TRDC was analyzed. Soil thermal resistivity at each of the points of comparison (dry, critical, and saturated) decreased as quartz content increased. Effect of particle shape on TRDC was analyzed based on sphericity and roundness of particles. Higher thermal resistivity was measured for prismoidal particle shapes as compared to spherical particle shapes. Soil packing with prismoidal particle shape included more voids than soil packing with spherical particle shape. Roundness of the 13 specimens ranged between 1.08 (well-rounded shape) and 1.13 (rounded shape). Soil thermal resistivity increased slightly with increasing roundness because moisture adsorption is enhanced when particle shape changes from a well-rounded shape to a rounded shape (Likos and Jaafar, 2013). In stepwise regression, D10 was the only significant factor in terms of ?sat, and D50 was only significant factor in terms of ?dry. The regression model for ?sat and ?dry resulted in R2 of 0.245 (24.5%) and 0.519 (51.9%), respectively. To investigate further statistical significance among the physical properties, a greater database of measurements for the TRDCs of sandy soils would be required. In comparing thermal resistivity with paramaters from the van Genuchten (VG) model, thermal resistivity increased slightly with the ? and n parameters, both of which are indicative of the shape of SWCC. However, one of the correlations?dry thermal resistivity to the ? parameter?decreased with the two SWCC parameters. Because of similar physical properties, however, increases in thermal resistivity were small. Therefore, additional tests with an expanded database of soils?including gravel, sand, silt, and clay?is recommended to more fully investigate the correlation between thermal resistivity and the VG parameters. Among the three points of analysis on the TRDC of the 13 sandy soils, ?soil at the fully dried condition was most affected by soil physical properties; to be specific, the dry thermal resistivity values ranged from about 150 ?C?cm/W to about 330 ?C?cm/W. Heat transfer in unsaturated soil systems directly depends on the matrix of solid particles and air voids, with large differences in resulting thermal resistivity. In contrast, thermal resistivity of the 13 specimens in terms of the physical properties changed only slightly at fully and partially saturated conditions (?soil ranged from about 40 ?C?cm/W to about 80 ?C?cm/W). These findings indicate that degree of saturation, particularly dry of the critical saturation, is the most significant factor for thermal resistivity of sandy soils with similar physical properties. A larger range of soil types with varying gravel content and percentage of coarse- and fine-sized sand is required to fully investigate the effect of soil physical properties on the TRDC at partially and fully saturated conditions.